الحماية الجنائية لبطاقات الدفع الإلكترونية وفقًا للقانون الإماراتي - Jamal Abdulrahman Jasem Alnuaimi; Hussein Azeemi Abdullah Thaid; Syahirah Abdul Shukor (Usuli Faqih Research Centre, 2024)
Non-Indexed Publication